A Situational Overview of Prenatal Screening Services in Bhutan - Yeshey Dorjey; Tashi Gyeltshen; Thinley Dorji; Don Eliseo Lucero‐Prisno III; Mimi Lhamu Mynak; Sonam Gyamtsho; Tashi Tshomo; Phurb Dorji (Public Health Challenges)
ABSTRACT Prenatal genetic testing is to determine the possibility of the fetus having a genetic aberration or birth defect. Prenatal screening consists of serum analytes screening with or without nuchal translucency (NT) scanning or with cell‐free DNA (CfDNA) screening. Prenatal screening is recommended for all pregnant women regardless of the duration of pregnancy and maternal age or baseline risk. It is not advisable to screen with serum analytes and CfDNA concurrently to avoid discordant results. In developed countries, prenatal testing has been a part of routine antenatal care for a long time with adopting newer methods of screening and testing. In Bhutan, since the integration of the Safe Motherhood Program into primary healthcare in 1994, there has been an unprecedented improvement in obstetric care services. Almost all pregnant women attend antenatal and postnatal care, and 98.5% of deliveries are attended by trained health workers. The maternal mortality has reduced to 53 in 2023 from 770 per 100,000 live births in 1984 and the neonatal dealth has reduced to 15.2 per 1000 live births in 2023. However, despite improvements in the care of pregnant women, many babies are detected with congenital anomalies, syndromes, and birth defects during the postnatal period. Bhutan, being an underdeveloped country, could not initiate any form of prenatal testing program except for the anatomical scanning performed at 18–22 weeks of gestation. Early ultrasound dating scans, limited anomaly scanning, and growth scanning are offered to all pregnant women. There is a need to start centralized prenatal testing services in Bhutan to provide a comprehensive package of obstetric care to pregnant women. In addition, legal rights for parents to terminate severely deformed fetuses or severe genetic diseases before 24 weeks of pregnancy need to be established.